Is restriction of intravenous fluid beneficial for septic shock in ICU patients? A meta-analysis of randomized controlled trials - Yushan Duan; Yue Yin; Jinxi Yue; Weihua Zhu; Xiumei Yang; Yiming Ma; Xiaohong Wan; Yuan Yang (BMC Anesthesiology)
Abstract Background In this study, we performed a meta-analysis to systematically evaluate how restrictive fluid resuscitation strategies, compared to conventional approaches, affect key clinical outcomes in adult patients with septic shock in the intensive care unit (ICU). The primary outcomes of our analysis included acute kidney injury incidence and ICU mortality, while the secondary outcomes encompassed mechanical ventilation requirement and ischemic event incidence. By comparing the efficacy and safety of the two strategies, this study provides evidence-based support for optimizing fluid management in patients with septic shock. Methods A systematic search of the PubMed, Cochrane Library, Web of Science, Embase, and CNKI databases was performed from inception to March 2024. Randomized controlled trials on restrictive fluid resuscitation for septic shock were included. Primary outcomes included acute kidney injury incidence and ICU mortality; secondary outcomes covered mechanical ventilation requirement and ischemic events. The meta-analysis was performed using Review Manager software (version 5.3). Results Five randomized controlled trials were included in this study, comprising 1972 patients. Compared to the conventional fluid resuscitation group, the restrictive fluid resuscitation group displayed no difference in acute kidney injury incidence (risk ratio (RR), 0.92; 95% confidence interval (CI), 0.79–1.07; P = 0.29; I2 = 0%), ICU mortality (RR, 1.00; 95%CI 0.9–1.12; P = 0.96; I2 = 0%), mechanical ventilation (RR, 0.96; 95%CI, 0.74–1.23; P = 0.74; I2 = 0%), and ischemic event rate (RR, 0.92; 95%CI, 0.31–2.68; P = 0.87; I2 = 58%). Limitations included the small number of included studies and moderate heterogeneity in ischemic event outcomes. Conclusion Although restrictive fluid resuscitation did not show superiority over conventional protocols in terms of clinical outcomes, it may represent a safe alternative for ICU patients with septic shock. Trial registration The study was registered on PROSPERO (CRD42024515869).